LOMBOK TOURISM SENTIMENT ANALYSIS WITH SOCIAL MEDIA MONITORING - Sari, Wulan Purnama; Irena, Lydia; Oktavianti, Roswita (ASPIKOM Jabodetabek Region, 2024)
Previous studies have shown that media monitoring provides significant benefits for the development of organizations or companies. The objective of this study is to analyze the sentiment surrounding Lombok tourism using social media monitoring. This research employs a quantitative method with a positivist paradigm and utilizes the Brand24 media monitoring tool. This research concludes that sentiment analysis towards Lombok and Mandalika tourism shows a dominant positive sentiment. Social media plays a key role in shaping perceptions of Lombok tourism, with Instagram being the dominant platform, while online news continues to have a big impact, with travel influencers playing a significant role in shaping tourist opinion